Archives and blank spots: scholarly perspectives for recovering Polish music (1794–1945) - Gmys, Marcin (Interdisciplinary Studies in Musicology, 2019)
In this article, the author tries to present the issue of blank spots in the history of Polishmusic since 1794 (the world premiere of Cud mniemany, czyli Krakowiacy i Górale [The supposedmirtacle, or Cracovians and highlanders] composed by Jan Stefani to the libretto of Wojciech Bogusławski is regarded as a symbolic beginning of national style in Polish music) up to the end of the SecondWorld War. It was a great period in history when Poland twice did not exist as a state (between1795 and 1918 and between 1939 and 1945). At the beginning the attention is drawn to the Polish music in the nineteenth century. Author describes new discoveries such as the Second Piano Quintet in E flat Major (with double bassinstead of second cello) by Józef Nowakowski (Chopin’s friend), and String Quartets op. 1 and monumentaloratorio Passio Domini Nostri Jesu Christi by Józef Elsner who was Chopin’s teacher in the Conservatory of Music in Warsaw (Elsner’s Passio discovered at the end of the twentieth century isregarded now as the most outstanding religious piece in the history of Polish music in the nineteenth century). Among other works author also mentions romantic opera Monbar (1838) by Ignacy Feliks Dobrzyński and first opera of Stanisław Moniuszko Die Schweitzerhütte (about 1839) written to the German libretto during composer’s studies at Singakademie Berlin. Addressing the issue of Polish music of the first half of the twentieth century author draws attention to the composer Eugeniusz Morawski regarded as the leading Polish author of programme music next to Mieczysław Karłowicz (unfortunately Morawski is still forgotten figure in the Polish musical life). Among others the importance of symphonic heritage of Feliks Nowowiejski, an author ofextremely popular in Europe during the second decade of twentieth century oratorio Quo vadis, is mentioned. At the end of article, the author takes up the problem of the enigmatic figure of Adolf Gużewski.The whole musical output of Gużewski, whose opera Dziewica lodowców [The Ice Maiden] was applauded in Warsaw and Russian opera houses in the second decade of the twentieth century, is now considered lost.